ANALISIS PERILAKU MINAT MENGGUNAKAN MOBILE PAYMENT DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL 3 : Studi pada Pengguna Aplikasi Pembayaran OVO - Emi Amelia, - (2019)
Emi Amelia (1707329), "Analisis Perilaku Minat Menggunakan Mobile Payment dengan Pendekatan Technology Acceptance Model 3 (Studi pada Pengguna Aplikasi Pembayaran OVO)". Di bawah bimbingan Prof. Dr. Hj. Ratih Hurriyati, MP dan Dr. H. Mokh. Adib Sultan,S.T MT. Penerimaan teknologi baru telah menjadi salah satu bidang terpenting dalam bidang teknologi informasi Dampak rendahnya minat konsumen utuk melakukan sistem pembayaran non tunai (online) menjadi masalah penting karena berhubungan dengan proses keputusan seseorang untuk menggunakan sistem pembayaran non tunai. Saat ini konsumen belum menggunakan secara optimal layanan yang ditawarkan oleh mobile payment. Upaya untuk memprediksi minat seseorang atau perilaku konsumen dalam penerimaan teknologi diantaranya dengan menggunakan pendekatan TAM 3 (Technology Acceptance Model 3). Tujuan penelitian ini dilakukan: Mengetahui gambaran behavioral intention, Perceived of Usefulness, Perceived Ease of Use menggunakan teknologi aplikasi mobile payment OVO oleh para konsumen, Mengetahui pengaruh Subjective Norm dan result demonstrability terhadap Perceived Usefulness, pengaruh computer selfefficacy, perceptions of external control, Computer Playfulness, Perceived Enjoyment, and Objective Usability terhadap Perceived Ease of Use, Perceived Usefulness dan Perceived Ease of Use terhadap Behavioral intention, Perceived Ease of Use terhadap Perceived Usefulness. Variabel bebas dalam penelitian ini adalah technology acceptance model 3 (X) perceived of usefulness, perceived ease of use dan behavioral intention (Y). Jenis penelitian yang digunakan adalah deskriptif verifikatif, dan metode yang digunakan adalah explanatory survey dengan teknik purposive sampling dengan jumlah sampel 150 responden. Teknik analisis data yang digunakan adalah path analysis dengan alat bantu software komputer SPSS 18.0. Berdasarkan hasil penelitian secara keseluruhan nilai perhitungan yang diperoleh melalui analisis jalur lebih besar dibandingkan dengan yang terdapat pada tabel. Artinya secara keseluruhan dan individu terdapat pengaruh yang signifikan dari technology acceptance model 3 terdapat satu dimensi yang tidak signifikan yaitu computer selfefficacy. Dalam penelitian ini terdapat temuan bahwa technology acceptance model 3 diantaranya subjective norm, result demonstrability, Perception of external, Computer Playfulness, Perceived enjoyment, Objective Usability, perceived of usefulness, perceived ease of use dan behavioral intention dinilai baik oleh responden. Kata kunci: technology acceptance model 3, perceived of usefulness, perceived ease of use dan behavioral intention Emi Amelia (1707329), "Analysis of Mobile Payment Behavioral Intention using Technology Acceptance Model 3 Approach (Study of OVO Payment Application Users)". Under the guidance of Prof. Dr. Hj. Ratih Hurriyati, MP and Dr. H. Mokh. Adib Sultan, S.T MT. The acceptance of new technology has become one of the most important fields in the field of information technology. The impact of the low interest of consumers to implement a system of non-cash payments (online) is an important problem because it relates to a person's decision process to use the non-cash payment system. Currently consumers have not used the services offered by mobile payment optimally. Efforts to predict someone's interest or consumer behavior in technology acceptance include using the TAM 3 approach (Technology Acceptance Model 3). The purpose of this study was: To know the description of behavioral intention, Perceived of Usefulness, Perceived Ease of Use using OVO mobile payment application technology by consumers, Know the Subjective Norm and the results of demonstrability on Perceived Usefulness, computer influence selfefficacy, perceptions of external control, Computer Playfulness Perceived Enjoyment, and Objective Usability to Perceived Ease of Use, Perceived Usefulness and Perceived Ease of Use to Behavioral intention, Perceived Ease of Use to Perceived Usefulness. The independent variable in this study is technology acceptance model 3 (X) perceived of usefulness, perceived ease of use and behavioral intention (Y). The type of research used is descriptive verification, and the method used is explanatory survey with purposive sampling technique with a sample of 150 respondents. The data analysis technique used is path analysis with SPSS 18.0 computer software. Based on the results of the overall research the value of the calculation obtained through path analysis is greater than that found in the table. This means that overall and individuals have a significant effect of technology acceptance model 3, there is one insignificant dimension, namely computer self-efficacy. In this study there are findings that technology acceptance model 3, including subjective norms, results demonstrability, Perception of external, Computer Playfulness, Perceived enjoyment, Objective Usability, perceived usefulness, perceived ease of use and behavioral intention are considered good by respondents. Keywords: Technology Acceptance Model 3, Perceived of Usefulness, Perceived Ease of Use and Behavioral Intention